(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The relationship between science and political decision-making has taken on different characteristics in recent years, both because of the growing importance of scientific issues and because of the evolution of technical tools to support decision-making. The pandemic experience has underlined the limits of the relationship and posed new problems in the regulatory process linked to scientific assessments. An analysis will therefore be made of the relationship between politics and technology, emphasising what might be the most suitable instruments to enable the scientific world to be adequately involved without, however, compromising the primacy of law.